2021
DOI: 10.1080/10717544.2021.1931558
|View full text |Cite
|
Sign up to set email alerts
|

Facile design of lidocaine-loaded polymeric hydrogel to persuade effects of local anesthesia drug delivery system: complete in vitro and in vivo toxicity analyses

Abstract: The principal goal of the present investigation was to enterprise new and effective drug delivery vesicle for the sustained delivery of local anesthetic lidocaine hydrochloride (LDC), using a novel combination of copolymeric hydrogel with tetrahydroxyborate (COP-THB) to improve bioactivity and therapeutic potential. To support this contention, the physical and mechanical properties, rheological characteristics, and component release of candidate formulations were investigated. An optimized formulation of COP-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The CCK-8 assay was performed in human fibroblast 3T3 cells for 24 h to validate the biocompatibility and nontoxicity of CS-GP hydrogel and CS-GP/PC polymeric hydrogel, as well as the anesthetic effects of BPV in the dosage form (Li et al., 2021 ). Although several researchers have demonstrated that GP is a safer cross-linker than glutaraldehyde, the compatibility of composite hydrogel formulations must be validated (Liang et al., 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…The CCK-8 assay was performed in human fibroblast 3T3 cells for 24 h to validate the biocompatibility and nontoxicity of CS-GP hydrogel and CS-GP/PC polymeric hydrogel, as well as the anesthetic effects of BPV in the dosage form (Li et al., 2021 ). Although several researchers have demonstrated that GP is a safer cross-linker than glutaraldehyde, the compatibility of composite hydrogel formulations must be validated (Liang et al., 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly applied anesthetics for administration via DDS are bupivacaine and lidocaine. 48 , 49 Encapsulation of these drugs in advanced DDSs, such as nano- and microparticles, should facilitate improvement of retention time in the body and prolonged drug release rates at the target site. 50 Local anesthetic delivery systems developed using a variety of inorganic materials (including microparticles, lipid nanoparticles, polymeric nanoparticles, or chitosan) have been comprehensively summarized in a recent review.…”
Section: Current Drug Delivery Systems For Local Anestheticsmentioning
confidence: 99%
“…This is connected to the filling of the network space with the drug molecules interacting with the polymer through the formation of hydrogen bonds, which, as a consequence, results in the compression of the hydrogel space. The porous structure is very important in biomedical applications of hydrogels, especially in tissue regeneration [12]. Lid occurs very often in the ionized form as lidocaine hydrochloride salt.…”
Section: Introductionmentioning
confidence: 99%